Isoform-Selective PI3K Inhibitors for Various Diseases - Bheemanaboina, Rammohan R.Y. (Current Topics in Medicinal Chemistry, 2020)
Phosphoinositide 3-kinases (PI3Ks) are a family of ubiquitously distributed lipid kinases that control a wide variety of intracellular signaling pathways. Over the years, PI3K has emerged as an attractive target for the development of novel pharmaceuticals to treat cancer and various other diseases. In the last five years, four of the PI3K inhibitors viz. Idelalisib, Copanlisib, Duvelisib, and Alpelisib were approved by the FDA for the treatment of different types of cancer and several other PI3K inhibitors are currently under active clinical development. So far clinical candidates are non-selective kinase inhibitors with various off-target liabilities due to cross-reactivities. Hence, there is a need for the discovery of isoform-selective inhibitors with improved efficacy and fewer side-effects. The development of isoform-selective inhibitors is essential to reveal the unique functions of each isoform and its corresponding therapeutic potential. Although the clinical effect and relative benefit of pan and isoformselective inhibition will ultimately be determined, with the development of drug resistance and the demand for next-generation inhibitors, it will continue to be of great significance to understand the potential mechanism of isoform-selectivity. Because of the important role of type I PI3K family members in various pathophysiological processes, isoform-selective PI3K inhibitors may ultimately have considerable efficacy in a wide range of human diseases. This review summarizes the progress of isoformselective PI3K inhibitors in preclinical and early clinical studies for anticancer and other various diseases.
Keywords: Thrombosis